Vector Analysis of Ionic Collision on CaCO3 Precipitation Based on Vibration Time History - Mangestiyono, W; Muryanto, S; Jamari, J; Bayuseno, A P (IOP conference series. Materials Science and Engineering, 2017)
Vibration effects on the piping system can result from the internal factor of fluid or the external factor of the mechanical equipment operation. As the pipe vibrated, the precipitation process of CaCO3 on the inner pipe could be affected. In the previous research, the effect of vibration on CaCO3 precipitation in piping system was clearly verified. This increased the deposition rate and decreased the induction time. However, the mechanism of vibration control in CaCO3 precipitation process as the presence of vibration has not been recognized yet. In the present research, the mechanism of vibration affecting the CaCO3 precipitation was investigated through vector analysis of ionic collision. The ionic vector force was calculated based on the amount of the activation energy and the vibration force was calculated based on the vibration sensor data. The vector resultant of ionic collision based on the vibration time history was analyzed to prove that vibration brings ionic collision randomly to the planar horizontal direction and its collision model was suspected as the cause of the increasing deposition rate.